E-Module Based on RME Approach in Improving the Mathematical Communication Skills of Elementary Students - Gistituati, Nurhizrah; Atikah, Nur (Jurnal Ilmiah Sekolah Dasar, 2022)
The low learning outcomes of mathematics are caused by the ineffectiveness of learning carried out by teachers. Innovation is needed that is in line with the development of communication technology. One of the innovations in the development of teaching materials in the form of e-modules that are contextualized with students' daily lives. The purpose of this study is to ditermined the effectiveness of the developed mathematics e-modules using the Realistic Mathematic Education (RME) approach in improving the mathematics communication skills of the elementary students. This study is a follow-up to the results of the validity and practicality tests of the e-module that has been developed. The development of e-modules using 4Ds models. In the previous studies, the validity of the developed e-module was tested through expert judgement, and the practicality was tested through individuals, small and large group trials. The effectiveness of the developed e-module was tested through pretest-posttest control group design using essay test; with 26 students at the experimental class and 24 students at the control class. Data were analyzed using t-test and N-gain score. The research found that the t score is 3,706; and the N-gain score is 63.81% for experimental class, and 58,85% for control class.Â  These results indicate that the use of developed e-modules based on the RME approach can improves student mathematical communication skills. Thus, it can be concluded that the developed e-module-based on RME approach is effective to improve the mathematical communication skills of the elementary students.